Laparoscopic Heller’s cardiomyotomy as the main method for treatment of achalasia cardia: an evaluation of treatment results - Kiosov, O. M.; Klymenko, A. V.; Danyliuk, M. B.; Kubrak, M. A. (Zaporozhye Medical Journal, 2024)
Achalasia is an esophageal motility disorder characterized by symptoms of dysphagia, regurgitation of undigested food, respiratory symptoms (nocturnal cough, recurrent aspiration, and pneumonia), chest pain, and weight loss. The aim: to evaluate the results of surgical treatment for achalasia cardia by the method of laparoscopic Heller’s cardiomyotomy in combination with Dor fundoplication. Materials and methods. To evaluate the treatment results of achalasia cardia by the method of laparoscopic Heller’s cardiomyotomy with Dor fundoplication, we analyzed 30 case histories of patients who were treated in the period from 2011 to 2022. Inclusion criteria were age 18 years or older, diagnosis of stage II, III cardia achalasia confirmed using instrumental examinations. Exclusion criterion was stage I achalasia. The mean age of the patients was 53.0 ± 15.3 years. In terms of sex, this group was almost equal, there were 14 (46.7 %) women and 16 (53.3 %) men. The average duration of the disease was 5.0 ± 1.2 years. To determine the degree of achalasia, we used the radiological classification of the distal esophageal morphology in achalasia and distinguished 4 stages. Based on this classification, stage II achalasia was detected in 24 (80.0 %) patients, and stage III – in 6 (20.0 %), p = 0.0007, U = 180.0. Results. All the patients were operated on as planned. The total duration of preoperative preparation in the hospital was 0.8 ± 0.2 days. The main method of treatment in this group was laparoscopic Heller’s cardiomyotomy with Dor fundoplication. Conclusions. Laparoscopic Heller’s cardiomyotomy with fundoplication is currently one of the most effective methods of treatment for achalasia cardia. Minimally invasive surgical treatment methods for achalasia are effective in most patients, however, recurrence of symptoms in the long term occurs in 10.0–20.0 %, leaving open the question of finding new effective methods for the treatment of this pathology.